Guanidinium functionalized polypeptide nanogels as the phosphate binder. (10th March 2017) - Sun, Yuling; Lyu, Xiangxue; Li, Zhibo; Huang, Yanbin
Abstract: Phosphate-binding particles are clinically used to reduce the phosphate level in patients with chronic kidney diseases. However, the binding efficiency of the current amino-functional polymers is low, resulting in high pill burden and low patient adherence. Here, we used polylysine nanogels with amino- and guanidinium-functional groups (PLL nanogel and GPLL nanogel), respectively, and experimentally proved that guanidinium is a much more efficient phosphate-binding group than the amino group at all the tested conditions. The phosphate binding amount of the GPLL nanogel is 60% higher than that of the PLL nanogel at pH 7, 55% higher at pH 2, and 30% higher in the presence of 150 mM NaCl. This guanidination strategy should also be applicable to non-polypeptide systems for anion sequestration. Though the difference of amino and guanidinium functional groups interacting with phosphate ions had been known in the literature, this is the first experimental study to directly compare their phosphate binding performance in clinically relevant conditions (e.g., crosslinked particle forms with all the other parameters controlled to be the same). Therefore, guanidinium functionalized polymers have the potential to become the new generation therapeutics. Graphical abstract: Abstract : Highlights: Phosphate-binding particles are clinically used to treat hyperphosphatemia. Currently-used amino-functional polymers unsatisfying in terms of binding efficiency. Guanidinium functionalized polymers can become the new generation therapeutics.